STATUS MUTU AIR SUNGAI GEDE KABUPATEN JEPARA - Lu’lu’ Farah Zulfa Nisrina; Eko Hartini (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Gede River used by people in Karangrandu Village, Jepara for farming, animal husbandry, and source for clean water. Since 2015, river with 3 km long already been polluted. The river condition are black, smell, and can cause itching. This pollution caused by industry development in Jepara. The aim of this study are determining status of Gede River water quality also identifying polluted source which affect to status of water quality. Sampling taken on three locations, observation and measurement done in three days, where each day take two times on 08.00 AM and 04.00 PM. Analysis of river water measured by Physics Parameter (temperature and TSS), Chemical Parameter (pH, COD, and DO) and Microbiology Parameter (Total of Fecal Coliform). Status definition of water quality on this research based on Pollution Index method according to Decree of Enviroment Minister No. 115 Year of 2003. Status of Gede River water quality is light polluted with the most pollution on upstream that come from textile industry waste, tofu and tempe industry waste, and domestic waste. Unsuitable parameter with quality standard are temperature, COD, DO, and Total of Fecal Coliform.Keywords : River Water, Status of Water Quality, Enviromental Quality Standard, Pollution, Parameter